Research on the Construction of a Reward and Commendation System for Volunteer Service with Chinese Characteristics - Ao, Xuyang (International Journal of Social Sciences and Public Administration, 2024)
Establishing a volunteer service reward and recognition system with Chinese characteristics is not only a theoretical issue but also a practical issue. This article will be based on studying foreign experience in volunteer service rewards and recognition, starting from the current situation and actual development needs of my country’s volunteer service work, and discussing the construction and improvement of the volunteer service reward and recognition system. It will be combined with reality, highlight characteristics, and focus on material and spiritual incentives. Incentives should be combined to establish a volunteer service reward and recognition system that is universal, normative, and consistent with volunteers’ motivations. Establishing a sound volunteer service reward and recognition system is a general trend for developing China’s volunteer service industry and the only way to achieve the "Two Centenary Goals."